2018
DOI: 10.1039/c8ta08273a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of advanced nanofiltration membranes with nanostrand hybrid morphology mediated by ultrafast Noria–polyethyleneimine codeposition

Abstract: Based on the host–guest interaction between anchored Noria and the amine monomer, high-performance nanofiltration membranes with nanostrand-hybrid morphology were fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 40 publications
4
63
0
Order By: Relevance
“…Benefitting from the increased water permeable areas of the crumpled ultrathin PA layers, the membranes showed unprecedented water permeation. Moreover, other research also verified the contribution of increased permeable areas within membrane separation layers to the permeance enhancement 11,22,24,25. Thinning the PA layers and increasing the permeable areas are both beneficial for elevating water permeance.…”
Section: Introductionmentioning
confidence: 74%
“…Benefitting from the increased water permeable areas of the crumpled ultrathin PA layers, the membranes showed unprecedented water permeation. Moreover, other research also verified the contribution of increased permeable areas within membrane separation layers to the permeance enhancement 11,22,24,25. Thinning the PA layers and increasing the permeable areas are both beneficial for elevating water permeance.…”
Section: Introductionmentioning
confidence: 74%
“…Upper-bound line represents the level of permeability and selectivity achieved by the currently prepared membranes. In order to illustrate the superiority of the asymmetric polyamide nanofilm between permeability and selectivity, we calculated related permeability/selectivity data of different types of polyamide membranes as currently reported in the literature, such as commercial polyamide membrane (Commercial membrane) 44 , crumpled polyamide membrane (IP with crumpled structure) 16,28,32 , polyamide membrane prepared by interlayer (Interlayer-IP) 20,21,26,[45][46][47][48] , traditional IP membrane (IP) 12,28,[49][50][51][52] , and mixed matrix polyamide membranes (MMMs) 14,[53][54][55][56][57][58][59][60] , as shown in Fig. 6a, b.…”
Section: Resultsmentioning
confidence: 99%
“…The study found that the porosity of the aromatic polyamide nanofilm is between 15 ± 2% and 32 ± 4% 31 . Incorporating hydrophilic additives during IP 28 , modifying the surface property of ultrafiltration support 32 , 33 or templated method 16 can form the polyamide nanofilm with high specific surface area. The latest research indicates that the wrinkle on the polyamide dense layers originates from the diffusion-driven instability of amine molecules during IP process, resulting in a high specific surface area 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the reaction of PEI, TA, and taurine helped the hydrophilic groups attach to PEI, which hindered the further diffusion of the PEI monomer and efficiently reduced the polyamide thickness. 43 These hydrophilic groups also absorbed water to form a water layer to change the surface tension between the aqueous phase and organic phase in the IP reaction to create the striped structure 44 (Fig. 1).…”
Section: Antifouling Property Of the Membranementioning
confidence: 99%